From the Natural Law to the Hermeneutic Universalism - Sancho, Jesús Conill (Pensamiento. Revista de Investigación e Información Filosófica, 2014)
This paper explains the problem of natural law, from its historical origins in the Greek thought and in Christianity, especially in the modern context. And it shows an alternative through the zubirian notion of person and the hermeneutical transformation of discursive ethics.